Responses of Aquatic Plants to Eutrophication in Rivers: A Revised Conceptual Model - O’Hare, Matthew T.; Baattrup-Pedersen, Annette; Baumgarte, Inga; Freeman, Anna; Gunn, Iain D. M.; Lázár, Attila N.; Sinclair, Raeannon; Wade, Andrew J.; Bowes, Michael J. (Frontiers in Plant Science, 2018)
Compared to research on eutrophication in lakes, there has been significantly less work carried out on rivers despite the importance of the topic. However, over the last decade, there has been a surge of interest in the response of aquatic plants to eutrophication in rivers. This is an area of applied research and the work has been driven by the widespread nature of the impacts and the significant opportunities for system remediation. A conceptual model has been put forward to describe how aquatic plants respond to eutrophication. Since the model was created, there have been substantial increases in our understanding of a number of the underlying processes. For example, we now know the threshold nutrient concentrations at which nutrients no longer limit algal growth. We also now know that the physical habitat template of rivers is a primary selector of aquatic plant communities. As such, nutrient enrichment impacts on aquatic plant communities are strongly influenced, both directly and indirectly, by physical habitat. A new conceptual model is proposed that incorporates these findings. The application of the model to management, system remediation, target setting, and our understanding of multi-stressor systems is discussed. We also look to the future and the potential for new numerical models to guide management.